2018
DOI: 10.5853/jos.2018.01263
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Adventitial Vasa Vasorum with Intracranial Atherosclerosis: A Postmortem Study

Abstract: Background and PurposeVasa vasorum (VV) have been believed to be rare or non-existent in small-caliber intracranial arteries. In a series of human cerebral artery specimens, we identified and examined the distribution of VV in association with co-existing intracranial atherosclerosis. MethodsWe obtained cerebral artery specimens from 32 consecutive autopsies of subjects aged 45 years or above. We scrutinized middle cerebral artery (MCA), vertebral artery (VA), and basilar artery (BA) for the presence of advent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Increased contrast wash-in could be expected as endothelium deficiency after symptoms presentation and greater vasa vasorum density in the vertebrobasilar artery. 34 Calcification exhibited a negative correlation with the entry and delivery of contrast agents into the plaque as validated by histology. 35 Limitations of this study need to be considered.…”
Section: Discussionmentioning
confidence: 88%
“…Increased contrast wash-in could be expected as endothelium deficiency after symptoms presentation and greater vasa vasorum density in the vertebrobasilar artery. 34 Calcification exhibited a negative correlation with the entry and delivery of contrast agents into the plaque as validated by histology. 35 Limitations of this study need to be considered.…”
Section: Discussionmentioning
confidence: 88%
“…Particularly in the elderly patient population that often suffers from increased vascular comorbidities, there are frequently additional atherosclerotic vessel wall changes that might cause difficulties in the interpretation [2,9]. Moreover, it can be assumed that the presence of vasa vasorum is associated with the progression of atherosclerosis [7,21]. While vasculitic affection and VWE caused by the presence of vasa vasorum usually manifest as smooth concentric lesions, atherosclerotic vessel wall lesions typically show an eccentric plaque-like configuration [9].…”
Section: Discussionmentioning
confidence: 99%
“…Another histopathologic study examined 30 human autopsy materials and found vasa vasorum in the proximal 1–2 cm of all VA and ICA [ 22 ], comparable to our imaging results. Another histopathologic study demonstrated that vasa vasorum were found in nearly half of all examined arteries with a significant higher prevalence in the VA compared to the basilar artery or the middle cerebral artery as well as a correlation between the existence and amount of vasa vasorum and the atherosclerotic disease burden in the VA [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vasa vasorum is a microvasculature network in vessel walls that delivers oxygen and nutrition (29) and transports inflammatory mediators (30)(31)(32) that could contribute to atherosclerosis. In 2018, Zheng et al (33) first reported the association between the density of intraplaque calcification and the presence of adventitial vasa vasorum in ex vivo VA specimens, indicating a mutual basis of calcification and ICAS. However, whether intimal or medial calcification is associated with vasa vasorum is yet unknown.…”
Section: Intimal Calcificationmentioning
confidence: 99%